Sistem Pendukung Keputusan untuk Menentukan Calon Pasangan Hidup Berdasarkan Status Sosial-Ekonomi Menggunakan SMART - Topan Setiawan; Yusuf Muhyidin (Jurnal Accounting Information System (AIMS), 2023)
In determining a potential life partner, each individual must have certain types or criteria, where one important aspect that must be considered is socio-economic status. Every married couple certainly hopes and wants to form a sakinah, mawaddah and warahmah family. By using a decision support system that can process data on the socio-economic status of a potential partner, each individual will get an overview of the best potential partner from the available alternative potential partners. One method that can be used is the Simple Multi Attribute Rating Technique (SMART). Based on the results of research that has been conducted with the criteria of education level, type of work, income level, amount of savings and number of siblings, it can be concluded that the SMART method is effective for objectively determining prospective spouses.